In Vitro Sealing Properties of Calcium-Enriched Mixture and Mineral Trioxide Aggregate Orifice Barriers during Intra-Coronal Bleaching - Moghadam, Negar; Abdollahi, Amir Ardalan; Aghabalayi Fakhim, Hoda; Borna, Zahra (Iranian Endodontic Journal, 2017)
Introduction: This study aimed at evaluating the sealing properties of calcium-enriched mixture (CEM) compared to mineral trioxide aggregate (MTA) as a cervical barriers in intra-coronal bleaching. Methods and Materials: In this in vitro study, endodontic treatment was performed on 60 extracted human incisors and canines without canal calcification, caries, restorations, resorption or cracks. The teeth were then randomly divided into two experimental groups and two control groups (n=15). Then, CEM cement and MTA were applied as 3-mm intra-orifice barriers in the test groups; a mixture of sodium perborate and 30% hydrogen peroxide bleaching agents were placed within the pulp chamber for one week. Dye penetration method was used to evaluate the sealing ability of agents. Statistical analysis was performed using SPSS software. The Kendall coefficient was used to evaluate inter-observer agreement. The chi-squared test was used for statistical analysis. Results: The results showed that the penetration rates of CEM and MTA were the same as positive control group, with no significant differences (P=0.673 and P=0.408, respectively). However, there was a significant difference between the negative control group and CEM and MTA groups (P=0.001 for both groups). In addition, the sealing ability of MTA and CEM cement were not significantly different (P=0.682). Conclusion: During intra-coronal bleaching procedures CEM cement can be used as a cervical barrier with sealing properties comparable to that of MTA. Keywords: Calcium-Enriched Mixture Cement; Cervical Barrier; Intra-Coronal Bleaching; Mineral Trioxide Aggregate